The Examination of Trade Off Theory and Pecking Order Theory to Capital Structure on Plantation Companies Listed in Indonesia Stock Exchange - Wijaya, Jesslyn; Cen, Ciptawan (ADI Publisher, 2021)
Plantation is a promising sector, but just like other firms, this sector will also face the financing problem. Capital structure determines the cost of capital and the risk assumed by the firm. Trade-off and Pecking order theory are the most common theory used to determine the capital structure. The objective of this research is to examine plantation companies tend to use trade-off theory or pecking order theory in determining the capital structure decision. This research used multiple linear regression analysis methods with capital structure as the dependent variable, and the asset structure, firm size, company growth, institutional ownership, effective tax rate, and non-debt tax shield as the independent variables.This is a quantitative research that uses secondary data from financial statements of plantation companies listed in the Indonesia Stock Exchange for 2014 to 2019. The sample was determined by using the purposive sampling technique and 5 out of 21 companies fulfill the sampling requirements. This study conducted observations for 6 years with a total of 30 research samples. The results of this research are both trade-off and pecking order theory are used and still relevant in the capital structure determination. Trade-off theory exerts more influence on capital structure decisions than pecking order theory. This is confirmed by the partial T-test where firm size, institutional ownership, effective tax rate, and non-debt tax shields suggest the use of trade-off theory, only asset structure indicates the tendency of pecking order theory.